The Yin and Yang of Tyrosine Kinase Inhibition During Experimental Polymicrobial Sepsis - Gonçalves-de-Albuquerque, Cassiano Felippe; Rohwedder, Ina; Silva, Adriana Ribeiro; Ferreira, Alessandra Silveira; Kurz, Angela R. M.; Cougoule, Céline; Klapproth, Sarah; Eggersmann, Tanja; Silva, Johnatas D.; de Oliveira, Gisele Pena; Capelozzi, Vera Luiza; Schlesinger, Gabriel Gutfilen; et al. (Frontiers in Immunology, 2018)
Neutrophils are the first cells of our immune system to arrive at the site of inflammation. They release cytokines e.g. chemokines to attract further immune cells, but also actively start to phagocytose and kill pathogens. In the case of sepsis this tightly regulated host defense mechanism can become uncontrolled and hyperactive resulting in severe organ damage. Currently, no effective therapy is available to fight sepsis, therefore novel treatment targets that could prevent excessive inflammatory responses are warranted. Src Family tyrosine Kinases (SFK), a group of tyrosine kinases, have been shown to play a major role in regulating immune cell recruitment and host defense. Leukocytes with SFK depletion display severe spreading and migration defects along with reduced cytokine production. Thus, we investigated the effects of Dasatinib, a tyrosine kinase inhibitor, with a strong inhibitory capacity on SFKs during sterile inflammation and polymicrobial sepsis in mice. We found that Dasatinib treated mice displayed diminished leukocyte adhesion and extravasation in TNF-α -stimulated cremaster muscle venules in vivo. In polymicrobial sepsis, sepsis severity, organ damage and clinical outcome improved in a dose-dependent fashion pointing towards an optimal therapeutic window for Dasatinib dosage during polymicrobial sepsis. Dasatinib treatment may therefore provide a balanced immune response by preventing an overshooting inflammatory reaction on the one side and bacterial overgrowth on the other side.